2007
DOI: 10.1016/j.pbb.2007.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peripheral and spinal histamine H3 receptors inhibits formalin-induced inflammation and nociception, respectively

Abstract: Pharmacological activation of histamine H3 receptors is known to reduce the release of inflammatory peptides, thereby reducing pain and inflammation, but the site(s) and mechanism(s) of these effects are currently unknown. The present study addressed these questions by examining the effects of the H3 agonist immepip and the H3 antagonist thioperamide on nociceptive behaviors and swelling produced during the rat formalin test. Systemic administration of immepip (5 and 30 mg/kg, s.c.) significantly attenuated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…In rats, a moderate dose of thioperamide given alone (15 mg/kg i.p.) had no effect on either phase of formalin-induced flinching; this dose blocked immepip's antiflinching activity (Cannon et al, 2007b). However, a more recent study in rats reported dosedependent reductions in late-phase, formalin-induced flinching responses after systemic administration of the highly selective, potent H 3 inverse agonist 6-[(3-cyclobutyl-2,3,4,5-tetrahydro-1H-3-benzazepin-7-yl)oxy]-N-methyl-3-pyridine carboxamide (GSK189254) (Hsieh et al, 2010b).…”
Section: Formalin-induced Nociceptionmentioning
confidence: 81%
See 4 more Smart Citations
“…In rats, a moderate dose of thioperamide given alone (15 mg/kg i.p.) had no effect on either phase of formalin-induced flinching; this dose blocked immepip's antiflinching activity (Cannon et al, 2007b). However, a more recent study in rats reported dosedependent reductions in late-phase, formalin-induced flinching responses after systemic administration of the highly selective, potent H 3 inverse agonist 6-[(3-cyclobutyl-2,3,4,5-tetrahydro-1H-3-benzazepin-7-yl)oxy]-N-methyl-3-pyridine carboxamide (GSK189254) (Hsieh et al, 2010b).…”
Section: Formalin-induced Nociceptionmentioning
confidence: 81%
“…In mice, oral BP 2-94 reduced both phases of formalin-induced licking and biting, but did not modify thermal (hot plate) responses . In a more recent rat study, systemic (subcutaneous) administration of the H 3 agonist immepip produced dose-dependent reductions (up to 70%) in both phases of formalin-induced flinching (Cannon et al, 2007b). These effects were mimicked by intrathecal immepip and blocked by systemic and intrathecal thioperamide.…”
Section: Formalin-induced Nociceptionmentioning
confidence: 90%
See 3 more Smart Citations